Modified cervicofacial flap for temporal region reconstruction post basal cell carcinoma excision - Lorensia Fitra Dwita; Al Hafiz (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Cervicofacial flap is considered to be the main choice for reconstruction of large defect in skin malignancies at head and neck such as basal cell carcinoma. Cervicofacial flap has a high successfull rate, due to the excellent vascularization, also the suitable matching in colour, thickness and texture. Purpose: To find out the result of reconstruction with modified cervicofacial flap after wide excision of basal cell carcinoma. Case report: A case of a 54-year-old-woman with basal cell carcinoma of the skin at right temporal region. Reconstruction of the temporal area was performed using a modified cervicofacial flap and followed by adjuvant radiotherapy, which resulted in a good outcome. Clinical Question: Is modified cervicofacial flap, the appropriate technique for defect reconstruction of post excision basal cell carcinoma at temporal region? Review method: Evidence based literature study of the procedure and outcome after reconstruction with modified cervicofacial flap through Cochrane library, Pubmed Medline, and hand searching. Result: Cervicofacial flap has a good vascularization, gave a blending colour, and almost similar healthy skin texture with its surrounding. Conclusion: Cervicofacial flap is the best technique for large defect in head and neck area, particularly in the face. Cervicofacial flap is also used for covering the cutaneous defect at facial and cheek region due to malignancy, particularly for basal cell carcinoma. It produces a good outcome. ABSTRAKLatar belakang: Flap servikofasial dianggap merupakan pilihan utama  untuk  rekonstruksi  defek yang luas pada keganasan kulit pada area kepala dan leher, seperti karsinoma sel basal. Flap servikofasial memiliki tingkat keberhasilan yang cukup tingg, karena jenis flap ini memiliki vaskularisasi yang baik serta memberikan keserasian warna, ketebalan dan tekstur yang sesuai. Tujuan: Mengetahui keberhasilan rekonstruksi dengan teknik flap servikofasial modifikasi pasca eksisi karsinoma sel basal. Laporan kasus: Seorang wanita berusia 54 tahun dengan diagnosis karsinoma sel basal kulit regio temporalis dekstra. Pada pasien telah dilakukan rekonstruksi daerah temporal dengan teknik flap servikofasialis modifikasi serta dilanjutkan dengan radioterapi adjuvan. Penatalaksanaan tersebut memberikan hasil yang memuaskan. Pertanyaan Klinis: Apakah teknik servikofasial flap modifikasi merupakan teknik yang tepat untuk menutup defek pasca eksisi karsinoma sel basal regio temporal? Telaah literatur: Berbasis bukti mengenai teknik dan hasil dari rekonstruksi dengan flap servikofasialis modifikasi melalui database Cochrane library, Pubmed Medline, dan pencarian manual. Hasil: Flap servikofasial memberikan vaskularisasi yang baik, warna yang sesuai dan mendekati tekstur kulit sehat sekitarnya. Kesimpulan: Flap servikofasial merupakan teknik flap terbaik untuk menutupi defek yang luas pada kepala dan leher, terutama pada area wajah. Flap servikofasial juga digunakan untuk menutup defek pada kulit wajah dan pipi akibat keganasan, terutama pada karsinoma sel basal, dan memberikan hasil yang baik.